Assessment on rearing and husbandry practices of indigenous goats in North Shewa Zone, Amhara Region, Ethiopia - Hailu Tilahun (Journal of Applied Animal Research, 2023)
The study was conducted for describing the rearing and husbandry practice of indigenous goats in the North Shewa zone. A total of 216 farmers were interviewed for the household survey. Data collected through a questionnaire (survey) were described by descriptive statistics using SPSS. The first objective of keeping goats in all districts was for income. Natural pasture (shrubs and bushes) and river water were the major sources of goat feeding and watering, respectively both in dry and wet seasons in the three districts. Among the interviewed goat keepers 94.4% in Berehet, 84.7% in Basona-Worena and 90.3% in Minjar-Shenkora had their own indigenous breeding male goat. The average flock size per monitored households in Berehet, Basona-Worena and Minjar-Shenkora districts was 14.70 ± 10.95, 7.43 ± 3.94 and 14.52 ± 11.36 goats, respectively. Growth rate, body conformation and coat colour for the breeding buck and litter size, body size or appearance and pedigree for does were the first, second and third selection criteria, respectively in all districts. Feed shortage, disease and labour shortage were the first, second and third-ranked constraints for goat production in the study districts, respectively.